INHERITANCE BEHAVIOUR OF QUANTITATIVE TRAITS IN LINSEED ( LINSEED (Linum usitatissimum L.) - NEHA SINGH; HEMANT KUMAR YADAV (The Bioscan, 2019)
Genetic components of variances were analysed to understand the nature of inheritance of important quantitative trait in linseed using half diallel mating involving 10 parental lines their 45F1 and 45F2 progenies. Significant values for additive (D) and dominance (H1, H2) genetic components of variance were observed for most of the traits in both generations. However, non-additive dominance type of gene action was predominant. Additive gene action was observed for all the traits except days to 50% flowering and plant height in both F1 and F2 generations. In the loci (H2<H1), majority of the traits showed unequal proportion of positive and negative genes with asymmetrical distribution among parental genotypes (H2/4H1<0.25). Significance of both additive and non-additive genetic variations suggested integrated breeding strategies with delayed selection for crop improvement.